Sex disparities in head & neck cancer driver genes: An analysis of the TCGA dataset. (May 2020) - Mundi, Neil; Ghasemi, Farhad; Zeng, Peter Y.F.; Prokopec, Stephenie D.; Patel, Krupal; Kim, Hugh Andrew Jinwook; Di Gravio, Eric; MacNeil, Danielle; Khan, Mohammed Imran; Han, Myung Woul; Shaikh, Mushfiq; Mendez, Adrian; et al.
Highlights: Females with HNSCC were found to have poorer overall survival compared to males. HPV-positive HNSCC was more prevalent in males compared to females. In HPV-negative HNSCC, BRWD3 mutations occurred in significantly more females. HPV-negative tumors harboring with BRWD3 mutations were found to have significantly worse overall survival. Sex differences exist in terms of mRNA abundance and copy number alterations. Abstract: Objectives: Survival in head and neck squamous cell carcinoma (HNSCC) has been associated with patient sex, typically with males experiencing poorer outcomes. It is unclear if this disparity is based in divergent tumor biology. We analyzed the TCGA HNSCC cohort to uncover disparities in the somatic single nucleotide variation (SNV), copy number alteration (CNA) and mRNA abundance profiles between males and females. Critically, we stratified our results by tumor HPV status to control for this significant confounder. Methods: SNV, CNA and mRNA abundance differences between males and females were compared separately for the HPV-positive (n = 67) and negative (n = 431) TCGA HNSCC cohorts. Overall survival outcomes were compared in males and females in both HPV-positive and HPV-negative subsets of patients. Results: Females were found to have poorer overall survival than males (p = 0.048), largely due to higher rates of HPV-positive disease among men. SNV analysis revealed that in HPV-positive disease, there were no differences by sex after accounting for the false discovery rate (FDR). In HPV-negative tumors, BRWD3 mutations occurred more frequently in the tumors of female patients compared to males after adjusting for the FDR (p = 0.02). Further, HPV-negative BRWD3 mutant tumors were found to have significantly worse 5-year overall survival compared to wildtype on multivariate analysis (p = 0.02). There were 88 heterozygous deletions and 14 amplifications that were differentially altered between male and female HPV-negative tumors and associated with expression changes. Pathway analysis of these genes revealed that tumors from males were enriched in five pathways including chemokine and phosphophatidylinositol signaling. Conclusions: Reanalysis of the TCGA HNSCC dataset stratified by sex revealed that males in this cohort had a significant survival advantage, due to a higher proportion of HPV-positive disease. Mutations in BRWD3 were more frequent in HPV-negative tumors of females and were associated with poorer overall survival. BRWD3 may represent a novel biomarker of patient outcomes, but will require additional validation.